Diagnosing Cardiac Amyloidosis: From Heart Failure to Electrical Storm. (21st June 2021) - Mathews, Adithya T.; Mirza, Abu-Sayeef; Bohra, Chandrashekar; Mathews, Akshay G.; Ritucci-Chinni, Philip; L. Weber, Jamie; W. Bulkeley, William; Siddique, Maqsood; Whitaker, David; Bowerman, Richard
Abstract : Cardiac amyloidosis is a condition when amyloid fibers are deposited in the extracellular space of the heart causing tachyarrhythmias, heart failure, or sudden cardiac death. We present a 71-year-old woman presenting with dyspnea on admission. Echocardiogram revealed diastolic heart failure and left ventricular hypertrophy with strain pattern concerning for an infiltrative process. She was discharged with diuretic therapy and scheduled for a cardiac magnetic resonance imaging. One week after discharge, she was readmitted with progressive shortness of breath and syncope. She was found to be in shock and had multiple episodes of cardiac arrest with both ventricular tachycardia and pulseless electrical activity. She developed electrical storm and eventually passed within 24 hours. Autopsy revealed gross cardiomegaly and left ventricular hypertrophy with Congo red staining revealing amyloid fibrils with apple-green birefringence. This case demonstrates the rapid progression of cardiac amyloidosis from acute-onset diastolic heart failure to uncontrollable ventricular tachycardia, and eventually death. We review the literature regarding multiple diagnostic modalities that facilitate the confirmation of cardiac amyloidosis.